2004
DOI: 10.1002/qsar.200420035
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility across Microwave Instruments: First Example of Genuine Parallel Scale up of Compounds under Microwave Irradiation

Abstract: One of the major issues associated to microwave assisted organic chemistry is reproducibility. In the present article we demonstrate that reproducibility of results can be obtained from commercially available single‐mode and multimode microwave reactors. In order to make an appropriate comparison of results obtained in both systems, alkylation reactions were used as a model. Based on the reproducibility observed in these experiments, parallel scale up of compounds in one irradiation experiment is reported for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…As mentioned above, the reproducibility of microwaveassisted reactions in solution has been unequivocally proved, allowing the efficiency of microwave chemistry to be combined with the productivity of the parallel approach [14][15][16][17][18]. Other studies, involving scale-up of microwavepromoted reactions -including solvent-free reactions-have been also reported [19][20][21][22].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As mentioned above, the reproducibility of microwaveassisted reactions in solution has been unequivocally proved, allowing the efficiency of microwave chemistry to be combined with the productivity of the parallel approach [14][15][16][17][18]. Other studies, involving scale-up of microwavepromoted reactions -including solvent-free reactions-have been also reported [19][20][21][22].…”
Section: Discussionmentioning
confidence: 86%
“…In recent years a number of reports have disclosed the reproducibility of results between monomode and multimode microwave instruments for solution chemistry [14][15][16][17][18]. Other authors, such are Hamelin [19] and Loupy [20] have showed how solvent-free reactions can be scale-up in monomode apparatus (Synthewave 402 to Synthewave 1000), and very recently Moseley [21] and Leadbeater [22] reported a comparison of commercial microwave reactors and show how different processing techniques can be used for scale-up microwave-promoted reactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The transformations included multicomponent chemistries, transition metal-catalyzed carbon-carbon cross-coupling protocols, solid-phase organic synthesis, and Diels-Alder cycloaddition reactions using gaseous reagents in prepressurized reaction vessels. Alcázar investigated the possibility of scaling up the synthesis of several compounds simultaneously in one irradiation experiment (Alcázar et al, 2004). This parallel approach would allow reduced reaction times in comparison with the sequential irradiation of single samples in single-mode instruments.…”
Section: Reproducibility In Parallel Microwave-assisted Reactionsmentioning
confidence: 99%
“…The other option is to use a batch‐type process. This could either involve using one large vessel7–9 or parallel batch reactors 10,11. Recently, our group has become interested in esterification reactions since these elementary yet multifaceted reactions find wide application in organic synthesis 12.…”
Section: Introductionmentioning
confidence: 99%